Les régimes enregistrés d’épargne-retraite - Garcia, Claude (Assurances)

(untitled) (HEC Montréal, 1984)
Retirement savings plan are being more and more developed in Canada. At a meeting of insurance brokers, Mr. Claude Garcia, Actuary, defined the various types of retirement savings plans. The reader will find his article of interest as he describes how various plans are designed to give the maximum return to the investor.